Negotiating Professional Identity Through AI: A Meta Analysis of Teachers’ Emotional Geography - Haryati, Sri (UICELE, 2026)
The increasing integration of Artificial Intelligence (AI) in education has significantly transformed teachers' professional practices and roles. While previous research has largely focused on technology adoption, AI literacy, and instructional effectiveness, limited attention has been given to how AI influences teachers' emotional experiences and professional identity. This meta-synthesis reviewed 42 empirical studies, including qualitative, quantitative, and mixed-method research published between 2020 and 2026, to examine the relationship between AI integration, emotional geography, and teachers' professional identity. Guided by the concept of emotional geography, the study explores how teachers experience and navigate emotional connections and tensions with students, colleagues, institutions, and AI technologies. Extending emotional geography to AI-mediated educational contexts, the analysis conceptualizes AI not merely as a technological tool but as a socio-technical actor that shapes teachers' emotional experiences, professional relationships, and perceptions of expertise. The findings indicate that AI integration generates both positive and negative emotional responses. On one hand, AI enhances teachers' confidence, creativity, instructional efficiency, and willingness to innovate. On the other hand, it raises concerns related to professional relevance, role ambiguity, technological dependence, and the changing nature of teacher expertise. The analysis further reveals that teachers actively reconstruct their professional identities by shifting from traditional knowledge transmitters to facilitators of learning, mentors of critical thinking, ethical guides, and human-centred educators within AI-supported learning environments. These identity negotiations are shaped by emotional interactions across multiple professional contexts. The study highlights the importance of addressing teachers' emotional needs and professional identity development to promote sustainable and meaningful AI integration in education.